Microwave spectroscopy of superfluid He II - Chishko, K.A.; Rybalko, A.S. (Физика низких температур, 2019)
Experimentally observed with dielectric disc resonator technique the resonant microwave absorptionamplification in superfluid He II below λ-point has been interpreted theoretically as a phenomenon in electrically active dielectric medium with low-energy excitations which exist near the ground state of the He–He interatomic bond due to fine structure of spin subsystem in condensed helium phase. The experimentally registered microwave resonant absorption line with fres = 180.3 GHz at T = 1.4 K and fres = 150.0 GHz at T = 2.1 K is closely related to the standard value of roton gap ∆/kB = 8.64 K (179.36 GHz). The measured temperature dependence of the resonant absorption demonstrates an excellent agreement with the corresponding neutron diffraction data for ∆(T) known from different literature sources. From the common point of view the obtained resonant absorption provides a typical example of the microwave spectroscopy which occurs widely among molecular systems with rotational and vibrational degrees of freedom, but for the first time discovered on as simple atomic matter as a superfluid helium. We explain the phenomenon as an effect of spin-phonon interaction within superfluid He II phase, and our theoretical estimation gives an upper limit ~ 250 GHz for the microwave resonant response of the system at T = 0. We interpret the dielectric 4 He superfluid as an electrically active working substance for low temperature MASER, and clarify the atomic mechanism of microwave absorption– amplification in the condensed helium phases. Резонансні поглинання–підсилення електромагнітної енергії НВЧ діапазону у надплинному He II при температурах нижчих λ -точки, що спостерігаються за допомогою техніки діелектричного дискового резонатора, інтерпретовано теоретично як ефекти у електрично активному діелектричному середовищі, яке вміщує низькоенергетичні збудження, що існують поблизу основного стану міжатомного зв’язку He–He завдяки тонкій структурі спінової підсистеми у конденсованих фазах гелію. НВЧ лінії резонансного поглинання fres = 180,3 ГГц при T = 1,4 К та fres = 150 ГГц при T = 2,1 К, які експериментально спостерігаються, однозначно корельовані зі стандартним значенням величини ротонної щілини ∆/ = 8,64 kB К (179,36 ГГц). Виміряна температурна залежність резонансного поглинання добре узгоджується з різними літературними даними по ∆( ) T . Згідно з загальноприйнятими уявленнями резонансне поглинання, яке спостерігається у НВЧ діапазоні, є ефектом, типовим для молекулярних систем з обертальними та коливальними ступінями свободи, однак про це явище вперше повідомлюється для такого простого атомарного середовища як надплинний гелій. Ми пояснюємо це явище як ефект спін-фононної взаємодії у надплинній фазі He II. Наша теоретична оцінка дає верхню границю ~ 250 ГГц щодо НВЧ резонансного відгуку системи при T = 0. Ми інтерпретуємо надплинний діелектрик 4 He як електрично активне робоче середовище для низькотемпературного MASERа та пояснюємо атомарний механізм НВЧ поглинання–підсилення у конденсованих фазах гелію. Резонансные поглощения–усиления электромагнитной энергии СВЧ диапазона в сверхтекучем He II при температурах ниже λ -точки, наблюдаемые с помощью техники диэлектрического дискового резонатора, интерпретированы теоретически как эффекты в электрически активной диэлектрической среде, содержащей низкоэнергетические возбуждения, существующие вблизи основного состояния межатомной связи He–He благодаря тонкой структуре спиновой подсистемы в конденсированных фазах гелия. Экспериментально регистрируемые СВЧ линии резонансного поглощения fres = 180,3 ГГц при T = 1,4 К и fres = 150 ГГц при T = 2,1 К однозначно коррелированны со стандартным значением величины ротонной щели ∆/ = 8,64 kB К (179,36 ГГц). Измеренная температурная зависимость резонансного поглощения демонстрирует прекрасное согласие с литературными данными по ∆( ) T . Согласно общепринятым представлениям, наблюдаемое резонансное поглощение в диапазоне СВЧ является эффектом, типичным для молекулярных систем с вращательными и колебательными степенями свободы, однако об этом явлении впервые сообщается для простой атомарной среды — сверхтекучего гелия. Мы объясняем это явление как эффект спин-фононного взаимодействия в сверхтекучей фазе He II. Наша теоретическая оценка дает верхнюю границу ~ 250 ГГц для СВЧ резонансного отклика системы при T = 0. Мы интерпретируем сверхтекучий диэлектрик 4 He как электрически активную рабочую среду для низкотемпературного MASERа и объясняем атомарный механизм СВЧ поглощения–усиления в конденсированных фазах гелия.